Platelet count trends in pregnant women who have pre-eclampsia with thrombocytopenia - Peprah, M A (Koranteng) (My University, 2016)
Background Pre-eclampsia can result in abnormal platelet function and count. Due to lack of resources and the subsequent over burden of specimens sent to our National Health Laboratory Services (NHLS), these results may not be obtained on time. Obstetricians and anaesthetists therefore make assumptions about platelet count in pre-eclamptic women – a common assumption is that a low platelet count will drop further as long as the woman remains pregnant. This may lead to unnecessary clinical and anaesthetist decisions in patient management. Objective This dissertation questions the predictability, at least while pregnancy continues, of platelet count trends in women who have pre-eclampsia with thrombocytopaenia, and also aims to identify factors associated with trends in platelet count in these women. Methods This study had a cohort design with data collected prospectively. Women who had thrombocytopenia as a complication of pre-eclampsia, with follow-up results while still pregnant, were included. Women were recruited at all three academic hospitals attached to the University of the Witwatersrand . No interventions were done, and all platelet count results used were from blood tests done as part of the management of each patient. Follow-up platelet counts were compared with initial platelet counts and observed for changes, using statistical tests for paired data, guided by a significance level of p<0.05. Results Thirty two women were entered into the study. For all the women, the median first platelet count on admission into the study was 112x109/L and the median follow-up platelet count was 99x109L, with no significant difference (Wilcoxon signed rank test for paired data, p=0.78). However, in the 12 women with raised aspartate aminotransferase (AST) levels on admission (AST≥40 U/L), the platelet count decreased by a mean of 19.7 x109/L (Student’s t-test for paired data; p<0.01). No other measured risk factors were associated with decreases in platelet count. Conclusion The platelet count in women with pre-eclampsia who have thrombocytopenia can be predicted only in the groups with raised AST or HELLP syndrome (p < 0.01).
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Medicine in Obstetrics and Gynaecology MMed (O&G) Johannesburg, May 2016